2023
DOI: 10.1055/s-0043-1772838
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation with Intravenous Direct Thrombin Inhibitors in Pediatric Extracorporeal Membrane Oxygenation: A Systematic Review of the Literature

Amy L. Kiskaddon,
Nhue L. Do,
Pamela Williams
et al.

Abstract: Although intravenous (IV) direct thrombin inhibitors (DTI) have gained interest in pediatric extracorporeal membrane oxygenation (ECMO), dosing and safety information is limited. The objective of this systematic review was to characterize DTI types, dosing, monitoring, and outcomes (bleeding and thromboembolic) in pediatric ECMO patients managed with IV DTIs. We conducted searches of MEDLINE (Ovid) and Embase (Elsevier) from inception through December 2022. Case reports, retrospective studies, and prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Amy has already previously published in STH, with a total of six papers, the most recent two as first author. 3 4 She is currently working in the Divisions of Pediatric Hematology and Cardiology, Department of Pediatrics, at the Johns Hopkins School of Medicine, and in the Department of Pharmacy at Johns Hopkins All Children's Hospital in the United States. She received her pharmacy degree from the University of Florida and completed pediatric pharmacy residency at the Texas Children's Hospital.…”
Section: Tablementioning
confidence: 99%
“…Amy has already previously published in STH, with a total of six papers, the most recent two as first author. 3 4 She is currently working in the Divisions of Pediatric Hematology and Cardiology, Department of Pediatrics, at the Johns Hopkins School of Medicine, and in the Department of Pharmacy at Johns Hopkins All Children's Hospital in the United States. She received her pharmacy degree from the University of Florida and completed pediatric pharmacy residency at the Texas Children's Hospital.…”
Section: Tablementioning
confidence: 99%
“…For the pediatric population, there are minimal data regarding use and dosing of direct thrombin inhibitors for ECMO, but Kiskaddon and colleagues have here performed a systematic review of the literature and they identified one prospective and 13 retrospective studies as well as several case reports. 12 Bivalirudin seems to be the most commonly reported (and probably used) direct thrombin inhibitor, but there was substantial variability in the dose regimens and the type of monitoring test used.…”
mentioning
confidence: 99%